Decolonising Intervention: International Statebuilding in Mozambique - Meera Sabaratnam (Kilombo: International Relations and Colonial Questions, 2017)
Building, or re-building, states after war or crisis is a contentious process. But why? Sabaratnam argues that to best answer the question, we need to engage with the people who are supposedly benefiting from international 'expertise'. This book challenges and enhances standard 'critical' narratives of statebuilding by exploring the historical experiences and interpretive frameworks of the people targeted by intervention. Drawing on face-to-face interviews, archival research, policy reviews and in-country participant-observations carried out over several years, the author challenges assumptions underpinning external interventions, such as the incapacity of 'local' agents to govern and the necessity of 'liberal' values in demanding better governance. The analysis focuses on Mozambique, long hailed as one of international donors' great success stories, but whose peaceful, prosperous, democratic future now hangs in the balance. The conclusions underscore the significance of thinking with rather than for the targets of state-building assistance, and appreciating the historical and material conditions which underpin these reform efforts.